Implementasi Perbanyakan Stek Pucuk Tanaman Kayu Putih dan Ampupu di Kelompok Tani Gandusari Hijau Magelang - Tri Suwarni Wahyudiningsih Tri; Ratna Suminar; Gian Sapta Adrialin; Farah Soviana (Jurnal Atma Inovasia, 2026)
This community service activity was carried out at the Gandusari Hijau Farmers Group, Bandongan District, Magelang Regency. The purpose of the service was to increase the capacity of farmers in terms of understanding and technical skills in vegetative propagation of non-endemic plants through shoot cuttings. The main problem partners faced was a low level of vegetative propagation skills. The first training session focused on the issue of propagating non-endemic plants. The second training session covered vegetative propagation practices using shoot-cutting techniques, with the Growthone application to stimulate root growth. The types of plants used as cutting materials were Melaleuca cajuputi, Eucalyptus urophylla, and forest rambutan (Saninten). Based on the results of the initial survey, the aspect of general knowledge about Eucalyptus had the highest score (43.06%). The aspect of knowledge about propagation materials and tools had the lowest score (37.04%). The aspects of technical skills in shoot cuttings, application, and development were obtained at 39.81% and 38.89%. The results of this community service activity have begun to be applied by the Gandusari Hijau Farmers Group for the propagation of other types of non-endemic plants, increasing technical skills for independent and sustainable propagation of shoot cuttings.